The Senjata otonom berbasis AI: Analisis literatur tentang etika, regulasi, dan ancaman keamanan: Literature Analysis on Ethics, Regulation, and Security Threats - FA IZAH, ALFINA NUR (Maliki Interdisciplinary Journal, 2025)
The development of artificial intelligence (AI) has driven significant transformations in the military, one of which is the emergence of AI-based autonomous weapons, or lethal autonomous weapon systems (LAWS). This article presents a literature review on three key dimensions of autonomous weapons: ethics, regulation, and security threats. From an ethical perspective, the existence of LAWS creates a moral dilemma because life-and-death decisions are transferred to algorithms that lack moral capacity. From a regulatory perspective, international humanitarian law does not explicitly regulate autonomous weapons, creating a normative vacuum. From a security perspective, autonomous weapons have the potential to trigger a global arms race and increase the risk of conflict escalation. This study emphasizes the urgency of developing a comprehensive international regulatory framework based on the principle of meaningful human control. This research is expected to enrich academic discourse on AI-based military technology and encourage a more balanced global policy discourse between technological innovation and humanitarian values.